A West African Model to Address Human Trafficking - Karenga, Paul V.I. Sidlawinde (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book describes the nature of trafficking in persons in West Africa, focusing on labor and sexual exploitation in the region, and recommends tailor-made solutions established by the Catholic Church in light of governmental authorities' failure to effectively combat this scourge of humanity. While states' efforts to fulfill their international obligations in developing anti-trafficking legislations are recognized, their failure to carry out prosecutions of offenders and ensure protection of the victims reveals that law alone is not a sufficient instrument for realizing human rights and improving people's lives. Faced with the sobering background of less than successful efforts by governmental entities to end the trade in humans, this research study recommends adopting essential elements of Catholic social teaching, which rests on the inherent dignity of human beings allowing the development of political, socio-cultural, and religious reforms that will increase the effectiveness of existing legislation designed to combat trafficking. This faith-based approach highlights the role that religion may play in fulfilling the discretionary provisions of the Palermo Protocol by promoting the welfare and protecting the life and dignity of the victims. Additionally, religion is composed of sound moral ethics that determine people's behavior to refrain from the sinful conduct of trafficking. It also creates a sense of ethical responsibility that promotes supply chain transparency and ethical purchasing as well as advocating social reforms and anti-trafficking legislations initiatives. In fact, the author's approach, may be a model for other regions in the world and will be of interest to scholars, law and policy makers, human rights advocates and law enforcement agents working in the field of trafficking in persons. .
Part I. The Problem of Trafficking in Persons and Respective Stakeholders -- Delimiting the Problem of Trafficking in Persons -- Relevant Actors and their Interests -- Part II. Legal and Institutional Framework Related to Trafficking in Persons -- Comparative Analysis between Slavery and Trafficking in Persons -- Understanding Trafficking in Persons in International Law,- Human Rights and Trafficking in Persons -- International Criminal Law and Trafficking in Persons -- Regional Anti-trafficking Efforts -- States' Obligations under International Human Rights Law in Relation to Trafficking in persons -- Implementation of Human Rights Obligations in Conjunction with the Palermo Protocol -- Part III. Trafficking in Persons in Light of the Social Teaching of the Catholic Church -- Trafficking in Persons in the Magisterium's Documents -- Principles of Catholic Social Teaching Related to Trafficking -- The Church's Contribution to Combating Trafficking in West Africa Recommendations and solutions.
Keywords: Human rights; Crime-Sociological aspects; Human Rights; Crime and Society; Politics and Human Rights